Analysis of Educational Values in the Novel Si Anak Savana by Tere Liye as Teaching Material for Literature Learning in High School - Muji Zain Naufal; Ade Apriyanto; Desi Ratnasari (Universitas Sebelas Maret, 2024)
Character education is a crucial aspect that must be imparted to pupils in schools. This is due to the fact that students, particularly adolescents, engage in a range of deviant behaviors as a manifestation of juvenile delinquency, including physical altercations, harassment, promiscuity, and similar activities. Contemporary reports in the media suggest that juvenile criminality has surpassed acceptable boundaries. The significance of character education in daily life can be exemplified through literary works, particularly novels. This research aims to analyze the educational values included in the novel